The role of epithelial cells in fibrosis: Mechanisms and treatment - Liuyi Luo; Wei Zhang; Siyao You; Xinyan Cui; Hua Tu; Qiao Yi; Jianjun Wu; Ousheng Liu (Elsevier, 2024)
Fibrosis is a pathological process that affects multiple organs and is considered one of the major causes of morbidity and mortality in multiple diseases, resulting in an enormous disease burden. Current studies have focused on fibroblasts and myofibroblasts, which directly lead to imbalance in generation and degradation of extracellular matrix (ECM). In recent years, an increasing number of studies have focused on the role of epithelial cells in fibrosis. In some cases, epithelial cells are first exposed to external physicochemical stimuli that may directly drive collagen accumulation in the mesenchyme. In other cases, the source of stimulation is mainly immune cells and some cytokines, and epithelial cells are similarly altered in the process. In this review, we will focus on the multiple dynamic alterations involved in epithelial cells after injury and during fibrogenesis, discuss the association among them, and summarize some therapies targeting changed epithelial cells. Especially, epithelial mesenchymal transition (EMT) is the key central step, which is closely linked to other biological behaviors. Meanwhile, we think studies on disruption of epithelial barrier, epithelial cell death and altered basal stem cell populations and stemness in fibrosis are not appreciated. We believe that therapies targeted epithelial cells can prevent the progress of fibrosis, but not reverse it. The epithelial cell targeting therapies will provide a wonderful preventive and delaying action.